Pengaruh Preheating Pada Cetakan Permanen Terhadap Sifat Fisis Dan Mekanis Besi Cor Kelabu - Cristy Martanta, Teguh, Agus Yulianto, ST, MT; Ir. Ngafwan, MT (2016)
Purpose of the research is to know effect of preheating of permanent ductile cast iron mold at 400C on physical and mechanical characteristics of grey cast iron. Solidification of the grey cast iron was monitored by using CE meter and after solidification was completed, the metal was tested for hardness test, metallographic test and chemical composition test. The research used tapered grey cast iron. Sixteen points of tests will be determined in the specimens of grey cast iron in order to know physical and mechanical characteristics in the predetermined points. Chemical composition test used JIS standards. Results of the research indicated that effect of preheating at temperature of 400C in permanent ductile iron mold with grey cast iron material produced varied hardness distribution. At the middle of diameter of the specimen, 5 points of tests taken bottom-up indicated values of hardness as follow: 219.54 Hv, 127.28 Hv, 150.80 Hv, 189.18 Hv and 144.54 Hv. At upside part of the middle of diameter to the side part were as follow: 144.54 Hv, 167.99 Hv, 159.50 Hv, 174.41 Hv and 176,23 Hv. At outer side that were taken bottom-up were as follow: 176.23Hv, 269.23Hv, 220.93 Hv, 258.03 Hv and 175,14 Hv. At lower side from edge to middle of the diameter were as follow: 175.14 Hv, 188.10 Hv, 190.97 Hv, 195.77 Hv and 216,54 Hv. Results of metal smelting test by using CE meter showed that initial temperature was 1356.80C, liquid temperature was 1155.40C, and solid temperature was 1113,60C in which the iron began to solid but it's color was still red until final temperature of 1060C when it solidified. Results of chemical composition test found 20 chemical elements with different level and micro structure observation found graphite and cementite structures. It can be known from results of the tests that the formed material was FC 150 grey cast iron with JIS standards. Key words: FC 150 grey cast iron, hardness CE meter, chemical composition.